Experimental demonstration of optical switch using gradient optical force - Ding, L. (2014)
A novel optical switch driven by gradient optical force is demonstrated, allowing weak light to switch a strong one. The proposed optically controlled switch achieves an extinction ratio of 28 dB with ~ns switching speed.